Makna Konotasi dan Denotasi dalam Lirik Lagu Himalaya karya Maliq D’essentials - Khairunnisa Lubis; M Ichasan Ardhian; Dina Ulva Jelita Rumahorbo; Frinawaty Lestarina Barus (Lingua Susastra, 2021)
Ferdinand De Saussure explains the meaning is concept that has or is present in a linguistic sign. Songs are a medium for expressing someone's feelings that are written in writing and have aesthetic values in these expressions. This study examines the meaning of a song, namely the Himalayan song sung by Maliq D'Essentials. The verse not only conveys the message openly, but there is a figurative meaning there. This research was conducted based on the author's observation of a song lyrics in the form of expressions of meaning, both denotative and connotative meanings. This research approach uses a semantic approach because semantics is a branch of science that studies the meaning of an expression. The method used in this research is descriptive qualitative method. The data collection technique used was the observation result technique, namely observing the Himalayan Maliq D'Essentials song as a research subject to study the meaning expression in each verse of the song with the depiction of the meaning of "Himalaya" as a figurative meaning expressed in denotation.